Prevalence and associated factors of depressive symptoms among first-year medical students at Hue University of Medicine and Pharmacy, Vietnam - Bao Tran Nguyen; Binh Thang Tran; Cao Khoa Dang; Thi Tra My Tran; Nu Hong Duc Vo (Journal of Public Health and Development, 2026)
Recent international evidence reveals a high burden of mental disorders among first-year students and highlights negative trajectories during medical training. The WHO-5 Well-Being Index is a concise, validated tool with robust measurement properties for academic settings. In Vietnam, previous studies have predominantly utilized the DASS-21, with limited evidence on WHO-5 screening for first-year medical students. This study aims to describe the prevalence of depressive symptoms (WHO-5) and analyze associated factors with a specific focus on gender differences. A cross-sectional study was conducted among 405 first-year medical and preventive medicine students (July–December 2024). Signs of depressive symptoms were defined as a WHO-5 score < 13. Descriptive statistics, Chi-square tests, and multivariable logistic regression were performed. The mean WHO-5 score was 14.2 (SD = 5.7); 36.5% of participants exhibited signs of depressive symptoms. Female students had a higher risk than males (AOR = 1.538; 95% CI = 1.010–2.342). This is the first study to apply the WHO-5 to first-year medical students in Central Vietnam, revealing a considerable proportion with depressive symptoms and significant gender disparities. Findings highlight the need for early WHO-5 screening and tailored interventions, especially targeting female students.